Terapi Range of Motion (ROM) pada Pasien Lansia Post Stroke dan Fraktur Tulang Panggul - Raissa Ardilla; Dara Febriana; Rahmawati Rahmawati (FKM UIN Sumatera Utara Medan, 2024)
ROM training is a form of exercise in the rehabilitation process which is considered to be quite influential in preventing disability in stroke sufferers. ROM therapy is divided into active ROM and passive ROM and is usually carried out in patients with decreased consciousness, patients unable to perform some or all range of motion exercises independently, patients on total bed rest or patients with total extremity paralysis. Complications that will occur in stroke sufferers include musculoskeletal complications that will occur, such as contractures, osteoporosis and falls. Everyone has risk factors for fracture because trauma can happen to anyone. The elderly are one of the age groups that have a higher risk of fracture. The aim of this manuscript is to provide Range of Motion (ROM) therapy to elderly patients post stroke and pelvic fracture. The nursing implementation provided to diagnose physical mobility disorders is passive ROM and active ROM therapy as well as providing education about preventing the risk of falls to minimize the risk of falls in the elderly. This nursing care is carried out 4 days in a row and is still routinely carried out independently for 15-20 minutes every morning and evening. After ROM therapy, there was an increase in muscle strength in the right lower extremity from 2222 to 3333 and there was a change from initially experiencing stiffness in the extremities to slowly increasing.